1999
DOI: 10.1177/0022022199030004006
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Culture and Human Resource Management Practices

Abstract: The Model of Culture Fit postulates that the sociocultural environment affects the internal work culture, which in turn influences human resource management practices. This model was tested by two independent cross-cultural studies comparing Indian and Canadian managers and employees. In assessing sociocultural environment and internal work culture, the “participant” technique was used in Study 1 (the respondents indicated their own beliefs and assumptions), and the “observant” technique was used in Study 2 (t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
153
0
14

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 224 publications
(172 citation statements)
references
References 20 publications
5
153
0
14
Order By: Relevance
“…The null hypothesis that organizational culture influences the job performance has been proved statistically. Overall influence of organizational culture on job performance as identified in a number of past researches carried out in non-Arabic cultures (Aycan et al, 1999;Lund, 2003;Ogbonna & Harris, 2000; Shehzad et al, 2013) have been substantiated in Saudi cultural environment as well. However, the impact of each element on the job performance was not found similar to these same researches.…”
Section: Resultsmentioning
confidence: 83%
“…The null hypothesis that organizational culture influences the job performance has been proved statistically. Overall influence of organizational culture on job performance as identified in a number of past researches carried out in non-Arabic cultures (Aycan et al, 1999;Lund, 2003;Ogbonna & Harris, 2000; Shehzad et al, 2013) have been substantiated in Saudi cultural environment as well. However, the impact of each element on the job performance was not found similar to these same researches.…”
Section: Resultsmentioning
confidence: 83%
“…Although people in small power distance cultures tend to value work autonomy and freedom, people in high power distance cultures, such as China, tend to take hierarchical inequalities for granted (Aycan, Kanungo, & Sinha, 1999;Earley & Stubblebine, 1989;Hofstede, 1991;Mak, 1998;Nasierowski & Mikula, 1998). It is also suggested that they have been exposed to, have become tolerant of, and have even submitted to authoritarian and command-based leadership for decades (Hofstede, 2001;Schermerhorn & Nyaw, 1990;Scott et al, 2003;Walder, 1986).…”
Section: Potential Deviations Of Conflict Management Styles In the Chmentioning
confidence: 99%
“…GLoBE provides two sets of these culture dimensions: one for society practices (i.e., how things are) and one for society values (i.e., how things should be). The Society Practices scores were used because these scores use respondents as key informants about their cultures, a method that can reduce the likelihood of responses being swayed by social desirability (Aycan, Kanungo, and Sinha, 1999). All nine GLoBE dimensions of culture were included in the multivariate analysis to perform a robust analysis.…”
Section: Methodsmentioning
confidence: 99%